Analysis of the Determinants of Job Satisfaction and Affective Commitment of School Administrative Staff in Deli Serdang Regency - Nurhamida, Nurhamida; Anwar, Yohny (PT. Multidisciplinary Press Indonesia, 2025)
This study aims to analyze the influence of: (1) competence on job satisfaction; (2) discipline on job satisfaction; (3) work motivation on job satisfaction; (4) competence on affective commitment; (5) discipline on affective commitment; (6) work motivation towards affective commitment; (7) job satisfaction with affective commitment; (8) job satisfaction in moderating competence on affective commitment; (9) job satisfaction in moderating discipline on affective commitment; and (10) job satisfaction in moderating work motivation on affective commitment to School Administration Staff in Senior High Schools in Sunggal Regency. The population of the study was School Administration Staff in Senior High Schools in Sunggal District with a sample of 136 people. The research method is a quantitative method with Smart-PLS analysis. The results of the study concluded: (1) the influence of the competence variable on job satisfaction is 27.1%; (2) the influence of the discipline variable on job satisfaction is 26.5%; (3) the magnitude of the influence of the work motivation variable on job satisfaction is 34.8%; (4) the influence of the competence variable on affective commitment is 12.5%; (5) the influence of the discipline variable on affective commitment is 71.4%; (6) the influence of the work motivation variable on affective commitment is 26.5%; (7) the magnitude of the influence of the job satisfaction variable on affective commitment is 16.6%; (8) the influence of the competence variable on affective commitment with job satisfaction moderation is 11.8%; (9) the influence of the discipline variable on affective commitment with job satisfaction moderation is 11.7%; and (10) the influence of the work motivation variable on affective commitment with job satisfaction moderation is 12.3%. Overall, the results of the study indicate that affective commitment is influenced by competence, discipline, and work motivation on job satisfaction by 74.0%; while the remaining 26.0% is determined by other factors.